A multi-country cohort database study to assess pregnancy and infant outcomes after potential maternal or paternal exposure to cladribine tablets in the treatment of multiple sclerosis: the CLEAR study methods and status update - Kerstin Hellwig; Melinda Magyari; Thomas M. MacDonald; Carolyn E. Cesta; Stig Wergeland; Maarit K. Leinonen; Asher Ornoy; Sandra Vukusic; Alexandra Lauer; Xiaolei Zhou; Alison Kawai; Rachel Weinrib; et al. (Therapeutic Advances in Neurological Disorders)
Background: Cladribine tablets are contraindicated during pregnancy; therefore, safety data on pregnancies exposed to this treatment are limited. CLEAR collects and describes pregnancy outcomes in this understudied population. Objectives: To describe the main features of the CLEAR study design, including the data sources and the methodological approach, and provide a status update. Design: CLEAR is a non-interventional, multi-database, comparative cohort study. Four cohorts are included: pregnancies of women with multiple sclerosis (MS) exposed to cladribine tablets (maternal cohort exposed); pregnancies of women with MS unexposed to any disease-modifying therapy (DMT; maternal cohort unexposed); pregnancies fathered by men with MS exposed to cladribine tablets; and pregnancies fathered by men with MS unexposed to any DMT. Methods: A staggered methodological approach, using data from Denmark, Finland, France, Germany, Norway, Scotland, and Sweden, will be applied to analyze the occurrence of major congenital anomalies (primary outcome) and selected pregnancy outcomes. The first interim analysis (performed using German pregnancy cohorts) was conducted when ⩾75 pregnant women (including 25 women from the maternal cohort exposed) were cumulatively reached across all participating countries. The end of the study period will be established once pregnancy counts reach 149 in the maternal cohort exposed and 298 in the maternal cohort unexposed in all countries combined, or 5 years after pregnancy counts are first assessed (whichever occurs first). Results: As of January 2024, data on pregnancies of women exposed to cladribine tablets ( n  = 28–36 (numbers are approximate due to masking of some counts)), and pregnancies of women unexposed to cladribine tablets ( n  = 2834) were available from Denmark, Finland, Germany, Scotland, and Sweden. Conclusion: The CLEAR study, using a staggered methodological approach, aims to provide further insight into the safety outcome data for cladribine tablets in pregnant women, as a regulatory commitment with the European Medicines Agency. Trial registration: EU PAS Register number, EUPAS25027.